Rating Hospital Performance in China: Review of Publicly Available Measures and Development of a Ranking System - Shengjie Dong; Ross Millar; Chenshu Shi; Minye Dong; Yuyin Xiao; Jie Shen; Xianqun Fan; Guohong Li (JMIR Publications, 2021)
BackgroundIn China, significant emphasis and investment in health care reform since 2009 has brought with it increasing scrutiny of its public hospitals. Calls for greater accountability in the quality of hospital care have led to increasing attention toward performance measurement and the development of hospital ratings. Despite such interest, there has yet to be a comprehensive analysis of what performance information is publicly available to understand the performance of hospitals in China. ObjectiveThis study aims to review the publicly available performance information about hospitals in China to assess options for ranking hospital performance. MethodsA review was undertaken to identify performance measures based on publicly available data. Following several rounds of expert consultation regarding the utility of these measures, we clustered the available options into three key areas: research and development, academic reputation, and quality and safety. Following the identification and clustering of the available performance measures, we set out to translate these into a practical performance ranking system to assess variation in hospital performance. ResultsA new hospital ranking system termed the China Hospital Development Index (CHDI) is thus presented. Furthermore, we used CHDI for ranking well-known tertiary hospitals in China. ConclusionsDespite notable limitations, our assessment of available measures and the development of a new ranking system break new ground in understanding hospital performance in China. In doing so, CHDI has the potential to contribute to wider discussions and debates about assessing hospital performance across global health care systems.